Osteoarthritis in obesity - Summary - Karol Jasiński; Ewa Dubniewicz; Paula Majewska; Alicja Staszek; Wiktoria Łoskot; Jan Szwech; Mateusz Matczak; Aleksandra Broda; Kacper Hoksa; Krzysztof Jodłowski (Journal of Education, Health and Sport, 2025)
Osteoarthritis (OA) is a slowly progressive joint disease that primarily affects articular cartilage and gradually causes pain, stiffness, and immobility. This problem negatively affects the quality of life of a large part of the population and consumes a significant part of the state budget. It ranks 11th in the list of global health issues in relation to disability. Primary OA occurs due to factors such as age progression, obesity, joint injuries, and anatomical features. Secondary OA frequently associates with other pathologies such as Paget's disease and osteoporosis. Of all the risk factors for KOA (knee osteoarthritis), obesity is the most critical since increasing body weight increases joint stress and hastens cartilage degradation. Weight loss, physical activity, management of symptoms forms in prevention and the management of KOA. Interventions of NSAIDs, glucocorticoids injections, and physiotherapy may help. Total knee arthroplasty remains the most effective treatment for patients with end-stage OA.